Phenotyping of improved rice lines and landraces for blast and sheath blight resistance - Dubey, A.K.; Pandian, R. T. P.; Rajashekara, H.; Singh, V.K.; Kumar, G.; Sharma, P.; Kumar, A.; Krishnan, S. Gopala; Singh, A.K.; Rathour, R.; Singh, U.D. (The Indian Journal of Genetics and Plant Breeding, 2016)
Globally,two major fungal diseases of rice,viz., blast caused by Magnaporthe oryzae and sheath blight incited by Rhizoctonia solani Kuhn. occur in all agro-ecosystems resulting in significant yield losses. In the present study, a set of 100 rice lines were evaluated for blast and sheath blight resistance. Twenty seven genotypes were identified to be resistant against M. oryzae isolate (Mo-ni-0066). However, evaluation of these genotypes with highly virulent M. oryzae Karnataka isolate (Mo-si-mnd) revealed that only two genotypes viz., Bhusan San and P1490-03 were resistant. Same set of genotypes were screened for sheath blight resistance. Four entries, viz., BPL7-12, BML27-1, BML 21-1 and Kajarahwa possess high degree of tolerance to sheath blight but none of the rice entries was completely resistant.